A new & accurate map of the North Pole with all the countries hitherto discovered situated near or adjacent to it as well as some others more remote. Drawn from the latest and best authorities and regulated by astronom.l observat.ns by Eman. Bowen. - Bowen, Emanuel ([London] : [Emanuel Bowen], [1752], 1752)
0-meridiaani: Lontoo. - Koordinaattiasteikko: N90°-55°[50°]. Lehti n:o 110. Julkaistu useissa eri kartastoissa.